The Sustainable COVID-19 Prevention for Health Workers in East Nusa Tenggara - Tat, Florentianus; Aty, Yoany Maria Vianney Bita; Herwanti, Elisabeth; Febryanti T. Banase, Emiliandry (Green Publisher Indonesia, 2023)
The continuous growth of Coronavirus disease 2019 (COVID-19) and the development of new virus variants is a significant health concern affecting various populations, specifically healthcare workers. Therefore, this study aimed to develop a model of Sustainable COVID-19 Prevention for Health Workers in East Nusa Tenggara (NTT). This quantitative study was carried out using a cross-sectional design, and the sample population comprised 2233 health workers in various health centers. Subsequently, a total of 300 were selected as participants based on the predetermined criteria. The analysis results showed that understanding standard operating procedure (SOP) and the purpose of preventive action had a significant effect on COVID-19 prevention behavior, with a significance value of p=0.001. Furthermore, the availability of human resources, drugs/health equipment, and budget had a significant influence. The results also showed that information, appreciation, emotional, equipment support, teamwork, socialization of actions, work coordination, and work culture affected COVID-19 prevention behavior, with a significance value of p=0.001. Based on the results, the variables with a significant effect on COVID-19 prevention behavior should receive adequate attention from the government.